2012
DOI: 10.1155/2012/596593
|View full text |Cite
|
Sign up to set email alerts
|

Primary Corneal Squamous Cell Carcinoma in a Dog: Clinical and Histopathological Evaluation

Abstract: An 8-year-old male pug with a 12-month history of a progressive nonpainful mass on the left cornea was evaluated. Ocular examination showed a severe bilateral keratoconjunctivitis sicca, pigmentary keratitis, and an exophytic irregular pink mass occupying approximately 75% of the total corneal surface of the left eye. A squamous cell carcinoma (SCC) was suspected on cytology, and clinical investigations showed no evidence of metastases. A transpalpebral enucleation was therefore performed, and the diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A report by [12] stated that neoplastic cells of adenocarcinoma were round to polygonal, pleomorphic with abundant cytoplasm, with irregularly shaped immature nuclei characterized by a high grade anisokaryosis and multiple nucleoli. Additionally [8] also reported that the cells of adenocarcinoma were basophilic, columnar and cuboidal with basal, prominent, hyperchromatic, condensed nuclei and moderate amount of cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…A report by [12] stated that neoplastic cells of adenocarcinoma were round to polygonal, pleomorphic with abundant cytoplasm, with irregularly shaped immature nuclei characterized by a high grade anisokaryosis and multiple nucleoli. Additionally [8] also reported that the cells of adenocarcinoma were basophilic, columnar and cuboidal with basal, prominent, hyperchromatic, condensed nuclei and moderate amount of cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Slides prepared from a canine renal macula densa tissue and a squamous cell carcinoma known to express COX‐2 served as positive controls. Evaluation of COX‐2 expression was quantified by a previously described scoring system based on estimation of the percentage of immunoreactive cells combined with an estimation of the staining intensity . The scoring system was as follows: 0, no staining; +1, weak diffuse cytoplasmic staining (may contain stronger intensity in <10% of the cells); +2, moderate to strong granular cytoplasmic staining in 10–90% of the cells; and +3, >90% of the cells stained with strong intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Two cases (0.04%), had been suferred of transitory serosanguineous or bloody unilateral nasal discharge in week following enucleation which disappeared spontaneously in a short period. Ascientific paper in dogs (20), had been reported minor bloody discharge from the nostril on the same side of the surgery in one dog.This sign resolved within 48hrs., without any treatment.…”
Section: Figure-8 Histopathological Section Show's Neoplastic Cells W...mentioning
confidence: 96%